Pesantren’s Politics and Policy in Bilingual Actualization Amidst The New Normal Era at PP Al-Iman Putri Ponorogo - Yuliani, Bustanul (IAIN Ponorogo, 2022)
The emergence of the da'wa movement shifted the political position in the Islamic struggle as an alternative political movement in realizing the idea of Islamic struggle. These new developments encourage the emergence of new developments of political thought among santri. Moreover, during the current Covid-19 pandemic, new political policies have emerged and rearranged the policy order to suit the current situation. Thus, a new habit emerges called the new normal in the pesantren setting. Likewise, one of the pesantren in Ponorogo, Pondok Pesantren Al-Iman Putri, has one of the featured programs for santri equipped with bilingual. It is Arabic and English. It is expected that santri will master Islamic religious knowledge and compete globally. The results showed that the politics and policies of pesantren implemented bilingualism during the new normal period at PP Al-Iman Putri Ponorogo. It prepared standard operating procedures enforced in it and adjusted to health protocols.